(untitled) (Medical Forum Monthly, 2020)
Objective: To study the Pattern of Renal Osteo dystrophy in chronic renal Disease patients. Study Design: Observational study Place and Duration of Study: This study was conducted at the Rawal Teaching Hospital Institute of Health Sciences, Rawalpindi and Idris Teaching Hospital Sialkot during Feb 2018 to Feb 2020. Materials and Methods: This study conducted on 100 patients The Demography data and laboratory finding was recorded on designed Performa. The informed consent was taken before taking the sample and clinical examination. The permission of Ethical Committee was considered before collection of data and get publishing in medical journal. The results were analysis by SPSS version 10. Results: The maximum incidence was diabetes mellitus patients 42(42%), minimum PCKD2(2%) and Undiagnosed patients 2(2%). In moderate renal disease Muscle pain was 14(53.83%) in male 12(46.15%) in female, Severe Renal disease 22(55%) male 18(45%) female were having muscle pain. Serum Calcium was normal 9.49+0.545, low 8.30 + 0.1732, high 11.32 + 0.487, Inorganic Phosphate the normal value 3.68 + 0.565, in high 6.83 + 1.66, Alkaline phosphatase normal value 216.66 + 51.86, High value 727.11 + 405.03, Intact Parathormone normal value 5.45 + 1.806, high value 25.09 + 16.338. Para thyroid hormone was normal to slightly elevated in low turnover, in high turnover it was Markedly Elevated. Conclusion: The most common histological type of renal Osteo dystrophy among dialysis and chronic kidney disease sick persons not on dialysis was hyperparathyroid bone disease; however, the presence of a dynamic bone disease was significant in both groups.